Behavioral nutrition in the care of person with mental disorders: case report - Pires, Leticia Ferreira (2022)
Introduction and objective: The behavioral approach is a nutritional tool used in clinical practice aimed at promoting change and facilitates compliance. It can be used in patients with mental disorders who have difficulties in adhering to conventional treatments. The aim of this study was to report the case of a patient with metabolic syndrome and mental disorders, user of a psychosocial care center. Materials and methods: This is a case report, with a descriptive design, with a narrative and reflective character. Nutritional monitoring was carried out for four months using a behavioral approach, whit motivational interview and nutritional counseling strategies, in order to encourage the patient to recognize his difficulties and promote effective changes in his eating behavior, through goals and action plans for their applicability. Discussion: The strategies used in this case were effective. The behavioral approach was able to produce changes in food choices and gradual weight reduction, in addition to being techniques that are easy to apply and adhere to in clinical practice. Conclusion: The nutritional interventions applied in this case was positive for changes in user's eating behavior, demonstrating to be a strategy that can be widely applied in situations similar to this study.